Tarzan and chain: exploring the ICO jungle and evaluating design archetypes - Nina M. Bachmann; Benedict Drasch; Gilbert Fridgen; Michael Miksch; Ferdinand Regner; André Schweizer; Nils Urbach (Electronic Markets, 2021)
The phenomenon of a blockchain use case called initial coin offering (ICO) is drawing increasing attention as a novel funding mechanism. ICO is a crowdfunding type that utilizes blockchain tokens to allow for truly peer-to-peer investments. Although more than 7bn has been raised globally via ICOs as at 2018, the concept and its implications are not yet entirely understood. The research lags behind in providing in-depth analyses of ICO designs and their long-term success. We address this research gap by developing an ICO taxonomy, applying a cluster analysis to identify prevailing ICO archetypes, and providing an outlook on the token value market performance for individual archetypes. We identify five ICO design archetypes and display their secondary market development from both a short-term and a long-term perspective. We contribute to an in-depth understanding of ICOs and their implications. Further, we offer practitioners tangible design and success indications for future ICOs.
Keywords: G15; G23; O33; 620; Blockchain; ICO; Taxonomy; Archetypes; Success analysis